(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The ever-changing terrain where collective empowerment propels economic growth is shed light on in Women Entrepreneurship via Self-Help Groups. Whether in a rural or metropolitan area, these organizations play an essential role as incubators, providing access to capital as well as the support, connections, and training that entrepreneurs need to launch and grow their businesses. While examining the many possibilities and threats that women-led companies confront, this investigation dives into the resiliency and creativity that define these organizations. This analysis aims to find avenues for boosting women’s economic involvement and empowerment by evaluating policy frameworks and support structures. Come explore the fascinating world of women entrepreneurs via self-help groups as we delve into their experiences, methods, and the power of transformation. Examine the ways in which self-help organizations encourage female entrepreneurs in this article.